KORELASI ANTARA KADAR INTERFERON-γ PLASMA DENGAN JUMLAH VIRAL LOAD DI PENDERITA HIV - Hermi Indita; Endang Retnowati; Erwin Astha Triyono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
The incidence of HIV is increasing in Indonesia and Asia as well, Indonesia is considered as the most rapid. One of the diagnostic toolsfor diagnosing HIV is by viral load. Lymphocyte T-CD8+ secreted IFN-γ will inhibit replication of HIV virus through the induction of antiviralprotein and the host immune response, which kills infected cells. An examination of plasma IFN-γ and viral load will be more convincingfor the treatment and/or to know the progressiveness of HIV & AIDS. The aim of this study is to know the correlation between plasma IFN-γand viral load in HIV patients. Forty two samples from HIV patients were collected at the Intermediate Care and Infectious Disease Unit ofDr. Soetomo Hospital, Surabaya from April to June 2011. The concentration of plasma IFN-γ was measured by ELISA (eBioscience) methodand the amount of viral load was measured using PCR Cobas Amplicor (Roche Diagnostics). The level of plasma IFN-γ in this study wasfound 11.4 pg/mL up to 576 pg/mL and the level of viral load was 589 copies/mL up to 510.000 copies/mL. The statistical analysis showedno significant correlation (p>0.05) between plasma IFN-γ level and viral load in HIV patients, and no correlation was found between IFN-γplasma and viral load in HIV patients.